Design and Construction of a Web-Based Crowdfunding Application Using the Laravel Framework - Foezi Arisandi SJ (Journal Collabits, 2025)
This research uses RAD analysis research method, diagram design using UML, system coding using PHP programming language and Mysql database. This research produces a web-based ordering system that is connected to a database so that order data can be stored properly. This research aims to design and build a web-based crowdfunding application to address inefficiencies in conventional ordering and donation systems, particularly in industrial environments. The study highlights the increasing importance of digital fundraising and the role of crowdfunding as an effective platform for connecting fund-seekers with potential donors. Using the Laravel framework and MySQL database, the system was developed to improve transparency, accessibility, and transaction management. The research applies the Waterfall development method and includes structured interviews and observation as part of the requirement-gathering process. The result is a functional, secure, and scalable web application that enables users to create, manage, and donate to campaigns with real-time tracking and integrated payment systems. This system enhances organizational outreach and improves the efficiency of donation and fund distribution processes.